Epidemiology and impact of HIV coinfection with Hepatitis B and Hepatitis C viruses in Sub-Saharan Africa - Matthews, P; Geretti, A; Goulder, P; Klenerman, P (Elsevier, 2014)
Human immunodeficiency virus (HIV), Hepatitis B (HBV) and Hepatitis C (HCV) are blood-borne viruses with potentially shared routes of transmission. In high-income settings, the impact of antiretroviral therapy (ART) on survival has unmasked chronic liver disease from viral hepatitis B or hepatitis C as a leading cause of morbidity and mortality in individuals with HIV infection. It is now feared that progressive liver disease may threaten the success of ART programmes in developing countries, where HCV or HBV testing and monitoring are not yet systematic among HIV-infected patients and ART use is generally blind to these co-infections. We set out to review recent data from Sub-Saharan Africa, in order to build a detailed and up-to-date picture of the epidemiology and emerging impact of HBV and HCV coinfection in countries at the heart of the HIV pandemic. There is a preponderance of HIV/HBV coinfection compared to HIV/HCV in this region, and significant caveats exist regarding the accuracy of published HCV seroprevalence surveys. Morbidity and mortality of coinfection is significant, and may be further enhanced in African populations due to the influence of host, viral and environmental factors. Careful scrutiny of the coinfection problem is vital to inform an approach to directing resources, planning public health initiatives, providing clinical care, and guiding future research. © 2014 Elsevier B.V.